2021
DOI: 10.3390/biom11081156
|View full text |Cite
|
Sign up to set email alerts
|

Novel Glutamate–Putrescine Ligase Activity in Haloferax mediterranei: A New Function for glnA-2 Gene

Abstract: The genome of the halophilic archaea Haloferax mediterranei contains three ORFs that show homology with glutamine synthetase (GS) (glnA-1, glnA-2, and glnA-3). Previous studies have focused on the role of GlnA-1, suggesting that proteins GlnA-2 and GlnA-3 could play a different role to that of GS. Glutamine synthetase (EC 6.3.1.2) belongs to the class of ligases, including 20 subclasses of other different enzymes, such as aspartate–ammonia ligase (EC 6.3.1.1), glutamate–ethylamine ligase (EC 6.3.1.6), and glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Furthermore, the enzymatic function of GlnA2 demonstrated in this work is similar to the function of GlnA2 in the halophilic archaea Haloferax mediterranei . It has been demonstrated that in this organism GlnA2 is not a GS but a glutamate-putrescine ligase involved in polyamine metabolism [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the enzymatic function of GlnA2 demonstrated in this work is similar to the function of GlnA2 in the halophilic archaea Haloferax mediterranei . It has been demonstrated that in this organism GlnA2 is not a GS but a glutamate-putrescine ligase involved in polyamine metabolism [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the primary enzymatic function of glnA2 in M. bovis and S. coelicolor remained unknown. Recently, GlnA2 has been described as a putrescine-glutamate ligase (HFX_01688) in the halophilic archaea Haloferax mediterranei , suggesting a role of GlnA2 in polyamine metabolism [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…These genes show a high homology with glutamine synthetase (GlnA), but it has been proposed that their role was different ( 66 ). Although the role of GlnA3 has not yet been described, GlnA2 is known to have glutamate–putrescine ligase activity and could be responsible for the growth of H. mediterranei in the presence of putrescine as the sole source of nitrogen and carbon ( 67 ). The transcriptional repression of both genes does not appear to be related to the decrease in ammonium concentration, as previous analyses of H. mediterranei ’s response to ammonium starvation did not reveal a reduction in the transcription of glnaA 2 or glnA 3.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Mycobacterium tuberculosis expresses three GS‐like enzymes (GlnA2 Mt , GlnA3 Mt , GlnA4 Mt ) [1] in addition to the archetypal GS (GlnA1 Mt or MtGS) and Pseudomonas aeruginosa contains seven additional GS‐like enzymes (PauA1‐7) [2] . Likewise, the actinobacterium Streptomyces coelicolor has three GS‐like enzymes (GlnA2 Sc , GlnA3 Sc , GlnA4 Sc ), [3] and the halophilic archaea Haloferax mediterranei harbours two GS‐like enzymes (GlnA2 Hm , GlnA3 Hm ) [4] . GlnA3 Sc and GlnA2 Hm were recently shown to be putative glutamate polyamine ligases.…”
Section: Introductionmentioning
confidence: 99%
“… [2] Likewise, the actinobacterium Streptomyces coelicolor has three GS‐like enzymes (GlnA2 Sc , GlnA3 Sc , GlnA4 Sc ), [3] and the halophilic archaea Haloferax mediterranei harbours two GS‐like enzymes (GlnA2 Hm , GlnA3 Hm ). [4] GlnA3 Sc and GlnA2 Hm were recently shown to be putative glutamate polyamine ligases. We recently identified GlnA4 from Streptomyces coelicolor to be an ATP‐dependent γ‐glutamylethanolamine synthetase with a putative mechanism similar to GS (Scheme 1 c).…”
Section: Introductionmentioning
confidence: 99%